Remineralization effects of two pediatric dentifrices and one regular dentifrice on artificial carious lesion in primary teeth: An in vitro study - Advani, Shweta (Medknow Publications & Media Pvt Ltd, 2014)
AIM: The aim of the following study is to know the efficacy of remineralization of two pediatric dentifrices and one regular dentifrice on artificial carious lesions in primary teeth. MATERIALS AND METHODS: A total of 21 teeth coated with nail varnish leaving a window of 1 mm were subjected to demineralization for 72 h. These 21 teeth were then sectioned into two equal parts with a diamond disc. The 42 sections obtained were then evaluated under the stereomicroscope and the demineralization values were noted. The 42 sections were divided into three groups: Group 1: Kidodent, Group 2: Cheeriogel, Group 3: Colgate Total and subjected to remineralization respectively for 7 days. The specimens were again evaluated under the stereomicroscope for the remineralisation values. RESULTS: All the three dentifrices showed remineralization with artificial carious lesions. Colgate Total showed higher remineralization rates compared with the other two pediatric dentifrices. Kidodent showed a slightly higher remineralisation rate compared with Cheeriogel which was not significant. CONCLUSION/HYPOTHESIS: The pediatric dentifrices also showed remineralization with artificial carious lesions. Hence, we conclude that, this amount of remineralization was more or less, when compared to the regular dentifrice which showed higher remineralization rates, which could lead to adverse effects, like fluorosis if not used judiciously. On basis of which we hypothetize: Pediatric dentifrices have an appropriate fluoride content, as required by the children, and also does not minimize the cariostatic effects.